USE OF APITOXIN AS AN INTERVENTION IN THE TREATMENT OF DERMATOLOGICAL INFLAMMATION - Lima, José Roberto da Cunha; Guimarães, Beatriz Gonçalves; de Lucena, José Wheslley Rodrigues; dos Santos, Nathanael Nascimento; Araújo, Paulo Miguel Simão; de Oliveira, Douglas Soares; Corrêa, Wendson de Ribamar Machado; de Carvalho, Katrine Nascimento; da Silva, Durcilene Alves (Seven Editora, 2024)
Bee venom (BV), produced by the species Apis mellifera, is one of the most recognized and widely studied natural toxins, with increasing use in integrative medicine. This venom contains a variety of chemicals, including peptides such as melittin, apamine, adolapin, and the peptide MCD, as well as enzymes such as phospholipase A2 (PLA2), hyaluronidase, acid phosphomonoesterase, and lysophospholipase. Amines such as histamine, dopamine, and norepinephrine are also present, which contribute to antimicrobial, anti-inflammatory, immunomodulatory, and anticancer properties. Studies suggest that it has promising pharmacological effects, especially in the treatment of inflammation. OBJECTIVE: This study aims to investigate the therapeutic effects of bee venom in the treatment of dermatological inflammations, exploring its potential as a natural alternative with proven anti-inflammatory properties. METHODOLOGY: A systematic review of the literature was carried out, focusing on primary articles and results of randomized controlled trials (RCTs) conducted in vivo and in vitro, published between 2014 and 2024. RESULTS: In mouse models of induced atopic dermatitis (AD), phospholipase A2 (PLA2), a BV-derived compound, has been shown to significantly reduce skin thickness and inflammatory cytokine levels, both in animal and human models, highlighting the importance of confirming its clinical applicability. As a result, therapies can include everything from the topical application of BV to the use of emollients and cosmetics with these compounds, based on their pharmacological properties. CONCLUSION: This review evidenced the potential of bee venom as a promising alternative in the treatment of dermatological inflammation, due to its anti-inflammatory and immunomodulatory properties. Studies in animal models and in vitro suggest that compounds such as melittin and phospholipase A2 (PLA2) inhibit inflammatory mediators and relieve symptoms of atopic dermatitis and acne. In addition, research indicates that BV can block inflammatory signaling pathways, such as NF-κB and MAPK, reinforcing its therapeutic potential in the management of skin inflammation, especially in topical applications. DOI:https://doi.org/10.56238/sevened2024.037-011